Validation of Microsimulation Models against Alternative Model Predictions and Long-Term Colorectal Cancer Incidence and Mortality Outcomes of Randomized Controlled Trials. (August 2020) - Lew, Jie-Bin; Greuter, Marjolein J. E.; Caruana, Michael; He, Emily; Worthington, Joachim; St John, D. James; Macrae, Finlay A.; Feletto, Eleonora; Coupé, Veerle M. H.; Canfell, Karen
Background . This study aimed to assess the validity of 2 microsimulation models of colorectal cancer (CRC), Policy1-Bowel and ASCCA. Methods . The model-estimated CRC risk in population subgroups with different health statuses, "dwell time" (time from incident precancerous polyp to symptomatically detected CRC), and reduction in symptomatically detected CRC incidence after a one-time complete removal of polyps and/or undetected CRC were compared with published findings from 3 well-established models ( MISCAN, CRC-SPIN, and SimCRC ). Furthermore, 6 randomized controlled trials (RCTs) that provided screening using a guaiac fecal occult blood test (Funen trial, Burgundy trial, and Minnesota Colon Cancer Control Study [MCCCS]) or flexible sigmoidoscopy (NORCCAP, SCORE, and UKFSST) with long-term follow-up were simulated. Model-estimated long-term relative reductions of CRC incidence (RR inc ) and mortality (RR mort ) were compared with the RCTs' findings.Results . The Policy1-Bowel and ASCCA estimates showed more similarities to CRC-SPIN and SimCRC . For example, overall dwell times estimated by Policy1-Bowel (24.0 years) and ASCCA (25.3) were comparable to CRC-SPIN (25.8) and SimCRC (25.2) but higher than MISCAN (10.6). In addition, ∼86% of Policy1-Bowel 's and ∼74% of ASCCA 's estimated RR inc and RR mort were consistent with the RCTs' long-term follow-up findings. For example, at 17 to 18 years of follow-up, the MCCCS reported RR mort of 0.67 (95% confidence interval [CI], 0.51–0.83) and 0.79 (95% CI, 0.62–0.97) for the annual and biennial screening arm, respectively, and the UKFSST reported RR mort of 0.70 (95% CI, 0.62–0.79) for CRC at all sites and 0.54 (95% CI, 0.46–0.65) for distal CRC. The corresponding model estimates were 0.65, 0.74, 0.81, and 0.61, respectively, for Policy1-Bowel and 0.65, 0.70, 0.75, and 0.58, respectively, for ASCCA .Conclusion . Policy1-Bowel and ASCCA 's estimates are largely consistent with the data included for comparisons, which indicates good model validity.